Ethical Responsibility of Public Administrators from the Legislator's View: An Analysis Based on a California Case Study. (2nd January 2018) - Emerson, Sandra; Wang, Jing
Abstract : This article reexamines the ethical responsibility of public administrators by investigating their role in policy process as perceived by legislators. The current dilemma for public administrators is how to pursue the public good in Madison's model of checks and balances. California legislators in the 2014 session were surveyed regarding four policy scenarios and their perceptions of the administrator's role in policymaking. Their responses are used to explore how legislators' perceptions of the administrator redefine the administrator's ethical environment. Factional factors (e.g., party divisions) may serve as an invitation for administrative input in the legislative policy process.